Determination of heavy metals in water sampled from selected vending machine in Kubang Kerian, Kelantan - Rahim, Nuraishah Abdul (Universiti Sains Malaysia, 2017)
Water is essential in sustaining life in all living organisms. Therefore, clean and safe drinking water is essential for healthy living. As many parts of the world becoming industrialized and urbanized, problems of water pollution are becoming more intensified with many areas of surface water and ground water are being contaminated with heavy metals. Due to that, the usage of vending machines are the alternative source of cleaner and safer drinking water for the household consumer nowadays. However, the safety and health aspect for these water vending machine with the respect to heavy metals contamination in particular is not known. It is the aim of this study to determine as well as to measure the presence and quantification of heavy metals in water sampled from selected vending machine in Kubang Kerian, Kelantan. The concentration levels of several selected heavy metals were tested using Flame Atomic Absorption Spectrometry (FAAS). The heavy metals elements tested were Zinc (Zn), Copper (Cu), Iron (Fe), Manganese (Mn), Lead (Pb) and Cadmium (Cd). It was found that 100.00% of the samples contained Mn. However, it was also found that only six samples which present 20 .00% that have the concentration level of Mn that is under the maximum acceptable value which set by the National Standard for Drinking Water Quality. The rest of the samples (80.00%) have the concentration exceed the limit which is 0.05 mg/L. Eighteen samples were found to have the concentration level for Cd that are non-compliance to the National Standard for Drinking Water where as there are five samples are comply with standard which is 0.005 mg/L. The excessive concentration of Pb in the water vending machine found that 50.00% of the samples did not comply with National Standard Drinking Water. The rest of the element which are Cu, Fe and Zn shown the concentration were under the standard and there were also found that 14 samples from Cu element, nine and six samples from Fe and Zn element respectively cannot be detected by FAAS respectively due to too low concentration of these elements. Water from water vending machines is unsafe for consumption due to the presence of heavy metals exceeding the minimum safety limit.